2018
DOI: 10.4067/s0717-95022018000100338
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Quercetin on Histomorphometric Changes in Kidney of Retinoid Acid-Treated Rat Fetuses

Abstract: KHAKSARY-MAHABADY, M.; RANJBAR, R.; NAJAFZADEH-VARZI, H.; MOHAMMADIAN, B. & GOHARI-BEHBAHANI, N.Protective effect of quercetin on histomorphometric changes in kidney of retinoid acid-treated rat fetuses. Int. J. Morphol., 36(1):338-344, 2018. SUMMARY:Retinoic acid, an active metabolite of vitamin A, plays essential signaling roles in mammalian embryogenesis. Prenatal rat fetuse exposure to retinoid induces some malformations in various organs, the most active and teratogenic metablolite is all-transretinoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The positive correlation between flavonoid intake and cancer incidence has been demonstrated in several in vitro and in vivo studies in addition to various clinical trials and meta-analyses. [99][100][101][102] Although the underlying chemopreventive and chemotherapeutic mechanisms are needed to be elucidated, flavonoids have been thoroughly investigated as to how they modulate various key elements in cellular signal transduction pathways and their effect on cell fate determination processes. [103][104][105] Most dietary flavonoids not only inhibit the growth of tumor cells but also promote cell differentiation by quenching oxidative stress and inflammatory response.…”
Section: Utilisation Of Nanomedicine In Varied Applications Of Flavonoidsmentioning
confidence: 99%
“…The positive correlation between flavonoid intake and cancer incidence has been demonstrated in several in vitro and in vivo studies in addition to various clinical trials and meta-analyses. [99][100][101][102] Although the underlying chemopreventive and chemotherapeutic mechanisms are needed to be elucidated, flavonoids have been thoroughly investigated as to how they modulate various key elements in cellular signal transduction pathways and their effect on cell fate determination processes. [103][104][105] Most dietary flavonoids not only inhibit the growth of tumor cells but also promote cell differentiation by quenching oxidative stress and inflammatory response.…”
Section: Utilisation Of Nanomedicine In Varied Applications Of Flavonoidsmentioning
confidence: 99%
“…It is known that several flavonoids can cross the placenta and may be accumulated in fetal tissue [96, 97]. It was found that quercetin affects pregnancy in animal model [97103]. According to Vanhees et al, when female mice were exposed to quercetin (302 mg/kg feed) from 3 days before conception until day 14.5 of gestation, no negative effects on placenta or fetal development were found [97].…”
Section: Quercetin Intake During Pregnancymentioning
confidence: 99%
“…Exposure to quercetin during pregnancy resulted in upregulation of genes involved in enzymatic antioxidant defense system of the liver of fetuses at day 14.5 of gestation [97]. Recently, Khaksary-Mahabady et al [103] have observed a protective effect of quercetin (75 mg/kg) on histomorphometric changes of kidneys of fetuses in pregnant rats treated with all-transretinoic acid (a teratogenic metabolite). Interestingly, Toumi et al [104] have shown that besides a protective effect with respect to hematological and behavioral anomalies in traumatized pregnant rats, quercetin (50 mg/kg per 6 days) may lastingly modulate behavior of their progeny.…”
Section: Quercetin Intake During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation